Biocatalytic Synthesis of Chiral N‐Functionalized Amino Acids. Issue 42 (21st September 2018) - Hyslop, Julia F.; Lovelock, Sarah L.; Sutton, Peter W.; Brown, Kristin K.; Watson, Allan J. B.; Roiban, Gheorghe‐Doru
Abstract: N‐Functionalized amino acids are important building blocks for the preparation of diverse bioactive molecules, including peptides. The development of sustainable manufacturing routes to chiral N‐alkylated amino acids remains a significant challenge in the pharmaceutical and fine‐chemical industries. Herein we report the discovery of a structurally diverse panel of biocatalysts which catalyze the asymmetric synthesis of N ‐alkyl amino acids through the reductive coupling of ketones and amines. Reactions have been performed on a gram scale to yield optically pure N ‐alkyl‐functionalized products in high yields. Abstract : Reductive amination space exploration : A new family of biocatalysts has been characterized for the asymmetric synthesis of N‐functionalized amino acids (see scheme), which are important building blocks for the preparation of bioactive molecules, including peptides. The structurally diverse biocatalysts catalyzed the reductive coupling of ketones and amines on a gram scale to yield the optically pure N ‐alkyl‐functionalized products in high yields.